2005
DOI: 10.1002/mrm.20399
|View full text |Cite
|
Sign up to set email alerts
|

129Xe spectra from the heads of rats with and without ligation of the external carotid and pterygopalatine arteries

Abstract: After rats inhaled hyperpolarized 129Xe gas, in vivo spectra from their heads revealed a dominant peak around 195 ppm, another easily resolvable peak near 189 ppm, a broad peak around 210 ppm, and two minor peaks around 198 ppm and 192 ppm. However, the source of each peak remains controversial. To further study the origin of each peak, we compared spectra obtained from the heads of normal rats with spectra taken from the heads of rats that had undergone ligation of the external carotid (ECA) and pterygopalati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 30 publications
6
40
1
Order By: Relevance
“…Xe signal dissolved in the rat brain appears at around 196 ppm; the peak around 190 ppm originates from non-brain tissue. 21,22 In accordance with the reported result, the MR image of HP 129 Xe acquired by chemicalshift-selection around 196 ppm accorded quite well with that of the entire region of the mouse brain in 1 H scout image, indicating that the signal originates from the brain parenchyma. 23 Therefore, in the present study, the main peak at around 196 ppm was assigned to the dissolved-phase HP 129 Xe originating from the mouse brain tissue.…”
supporting
confidence: 88%
“…Xe signal dissolved in the rat brain appears at around 196 ppm; the peak around 190 ppm originates from non-brain tissue. 21,22 In accordance with the reported result, the MR image of HP 129 Xe acquired by chemicalshift-selection around 196 ppm accorded quite well with that of the entire region of the mouse brain in 1 H scout image, indicating that the signal originates from the brain parenchyma. 23 Therefore, in the present study, the main peak at around 196 ppm was assigned to the dissolved-phase HP 129 Xe originating from the mouse brain tissue.…”
supporting
confidence: 88%
“…Although earlier studies evidenced the presence of 5 129 Xe NMR peaks in the rat head 19, 20, only two or three peaks have been previously detected from 129 Xe in the human head from spectra of significantly lower SNR and spectral resolution than those in this study 4, 18. Our results should provide a useful reference for future 129 Xe NMR spectroscopy studies of the human brain.…”
Section: Discussioncontrasting
confidence: 38%
“…Kershaw et al and Nakamura et al 19, 20 observed five peaks in 129 Xe spectra from the rat head, which they attributed to jaw muscle (187–191 ppm), white matter (191–194 ppm), gray matter (193–197 ppm), fat tissue outside the brain (197–201 ppm), and red blood cells (210 ppm). The feasibility of imaging rat brain using HP 129 Xe CSI was demonstrated by Swanson et al 16.…”
Section: Introductionmentioning
confidence: 99%
“…The HP 129 Xe gas peak was set as 0 ppm for reference. The two clearly prominent peaks at 194.7 ppm and 189 ppm were identified as dissolved HP 129 Xe in the brain tissue and non-brain tissue, respectively, and a broad peak around 209.5 ppm was identified as dissolved HP 129 Xe in the blood, on the basis of the results of Nakamura et al (20). The identities of the smaller peaks at 191.6 ppm and 197.8 ppm are still unknown and remain to be determined.…”
Section: Discussionmentioning
confidence: 97%
“…Spectroscopic scans using two T 1 protocols (see below) were started 6 s after the end of delivery of HP 129 Xe. The 6 s delay was to make sure that the delivery of xenon to the brain had ceased, because xenon residence time in the lung and the transportation time of blood from the lung to the brain are both less than 5 s (20).…”
Section: Nmr Methodsmentioning
confidence: 99%